Single-cell RNA sequencing and spatial transcriptomics of esophageal squamous cell carcinoma with lymph node metastases - Wei Guo; Bolun Zhou; Lizhou Dou; Lei Guo; Yong Li; Jianjun Qin; Zhen Wang; Qilin Huai; Xuemin Xue; Yin Li; Jianming Ying; Qi Xue; et al. (Experimental and Molecular Medicine)
Abstract Esophageal squamous cell carcinoma (ESCC) patients often face a grim prognosis due to lymph node metastasis. However, a comprehensive understanding of the cellular and molecular characteristics of metastatic lymph nodes in ESCC remains elusive. In this study involving 12 metastatic ESCC patients, we employed single-cell sequencing, spatial transcriptomics (ST), and multiplex immunohistochemistry (mIHC) to explore the spatial and molecular attributes of primary tumor samples, adjacent tissues, metastatic and non-metastatic lymph nodes. The analysis of 161,333 cells revealed specific subclusters of epithelial cells that were significantly enriched in metastatic lymph nodes, suggesting pro-metastatic characteristics. Furthermore, stromal cells in the tumor microenvironment, including MMP3+IL24+ fibroblasts, APLN+ endothelial cells, and CXCL12+ pericytes, were implicated in ESCC metastasis through angiogenesis, collagen production, and inflammatory responses. Exhausted CD8+ T cells in a cycling status were notably prevalent in metastatic lymph nodes, indicating their potential role in facilitating metastasis. We identified distinct cell-cell communication networks and specific ligand-receptor pathways. Our findings were validated through a spatial transcriptome map and mIHC. This study enhances our comprehension of the cellular and molecular aspects of metastatic lymph nodes in ESCC patients, offering potential insights into novel therapeutic strategies for these individuals.